2014
DOI: 10.5152/tud.2014.76753
|View full text |Cite
|
Sign up to set email alerts
|

An unusual complication of a double-J ureteral stent: Renal parenchymal perforation in a solitary kidney

Abstract: Double-J ureteral stenting is commonly used in urological practice and has various complications. We report a patient with a renal parenchymal perforation and perirenal hematoma due to a double-J ureteral stent in a solitary kidney. This complication of ureteral stents is rarely observed and is life-threatening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In our study, the most common was the placement of the proximal end into the ureter, but we also experienced 3 cases with placement into retroperitoneum, one case with parenchymal perforation and hematoma. Renal parenchymal perforation is rare but life-threatening [ 6 ]. A malpositioning complication like intravascular migration of double J stent, ureteroarterial fistula, hemoperitoneum, or knotted stent has been reported as very rare [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most common was the placement of the proximal end into the ureter, but we also experienced 3 cases with placement into retroperitoneum, one case with parenchymal perforation and hematoma. Renal parenchymal perforation is rare but life-threatening [ 6 ]. A malpositioning complication like intravascular migration of double J stent, ureteroarterial fistula, hemoperitoneum, or knotted stent has been reported as very rare [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports note the development of a subcapsular hematoma developing after a double-J stent placement [ 7 , 8 ]. Other reports noted the development of a perinephric hematoma following renal parenchyma perforation or forniceal rupture from an obstructive ureteral calculus [ 9 , 10 ]. To our knowledge, there are no cases of isolated perinephric hematomas developing after double-J ureteral stent placements.…”
Section: Discussionmentioning
confidence: 99%
“… 1 They usually present with a urinoma or hematoma. 1 , 3 Although ureteral double J stenting is a safe procedure, serious complications requiring emergency intervention like hemoperitoneum, renal vein perforation and ureteroarterial fistula have been reported. 1 , 4 Dundar et al reported the first case of renal parenchymal perforation with subcapsular hematoma due to double J stent in a patient with a solitary kidney and was managed by repositioning the stent.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Two more similar cases of renal parenchymal perforation with perirenal collection (hematoma/urinoma) were reported by Nomikos et al, Aditya Pradhan et al and Gönülalan U et al which were managed by stent repositioning or removing it. 1 , 3 , 4 Presenting with a renocolic fistula is a very rare complication post double J stenting for relieving ureteral obstruction due to urinary calculi and a thorough review of literature revealed no similar reports. Our patient was managed endourologically by replacing with a new double J stent (which was removed cystoscopically after one month), patient is under regular follow-up and is doing well with no complications.…”
Section: Discussionmentioning
confidence: 99%